Hydrogen Adsorption of Ti-Decorated Boron Nitride Nanotube: A Density Functional Based Tight Binding Molecular Dynamics Study - Mananghaya, Michael Rivera (Archīum Ateneo, 2018)
The hydrogen adsorption capabilities of Titanium functionalized single-walled BN nanotubes (BNNTs) with B–N defects was assessed by density-functional theory tight binding (DFTB) method. According to the DFTB molecular dynamics simulations, the BNNT structures were thermodynamically stable, the Ti atom once incorporated with the B–N defects present in BNNT (Ti–BNNT) protrudes to the external surface of the BNNT sidewall. The titanium atoms does not agglomerate to form any metal clusters. The results revealed that at 77 K and 10,000 KPa, the H2–Ti–BNNT has a gravimetric hydrogen storage capacity above 7 wt% ideal for department of energy specifications. Further calculations suggest that the Ti–BNNT has a good affinity towards H2 molecules and under low pressure of 500 KPa. The H2 stays close to the Ti metal due to its partially cationic character with some H2 attaching itself at the BNNT surface due to heteropolar bonding. H2 atoms is physisorbed in analogous to or resembling something molecular near the Ti sites which gives rise to a significant storage capacity for H2 in these modified BNNT.